ChemInform Abstract: A Regio‐ and Stereoselective Entry to (Z)‐β‐Halo Alkenyl Sulfides and Their Applications to Access Stereodefined Trisubstituted Alkenes. Issue 37 (16th September 2014) - Liu, Ge; Kong, Lichun; Shen, Ji; Zhu, Gangguo
Abstract The base‐promoted hydrothiolation of bromoalkyne (I) leads to (Z)‐bromo vinylic sulfides (III), which are converted into (Z)‐trisubstituted alkenes (VII) and (VIII) by Suzuki coupling and a subsequent reaction of resulting alkenyl sulfides (V) with Grignard reagents (VI).